الضمانات القانونية الدولية لترقية حقوق الإنسان وحمايتها - خشخوشة، سكينة حسين الهادي (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2018)
The increased awareness on the dangers that face Man and the subsequent infringements on his rights and freedom has motivated the researcher to the topic of human rights; especially after its maximized role in keeping international peace and security through United Nation's agreement. This matter raised the international community's concern on maintaining these rights after they have been transferred from local to international aspect. But the outputs are still unfortunately below expectations. Therefore, the researcher decided to focus on the topic “International legal guarantees to promote and protect human rights”. The problem statement focused on the following: To what extent are international legal guarantees to promote and protect human rights and their operating mechanisms available and to what extent can then be applied in reality to respect nations' specialities and to avoid inequality? The question is divided into the following sub-questions: What are the reasons for human rights infringements through international mechanisms and guarantees which can protect them? Is the solution in guarantees or mechanisms or both? The study aimed at tracking the development of the movement of human rights international law and analyzing and evaluating the role of legal international laws and its authorities in supervising and monitoring the protection of human rights. The limitations of the study are represented in the international legal agreements and mechanisms to protect human rights under the purview of the United Nations. The methodology included analysis of texts, documents and bureau studies through adopting the historical approach to present the human rights international agreements based on the descriptive approach and deductive approach for analyzing the relative legal international texts and agreements. The researcher followed the following plan: the first chapter presents the statement at the problem, the second chapter includes the theoretical framework which points out the terms and characteristics of human rights international law and its affecting factors, the third chapter comprises the basic and subsequent roles of the United Nation to protect and promote rights, the fourth chapter illustrates the specifications and operational mechanisms of specified international organizations and specific international agreements in promoting and protecting human rights. Finally, the conclusion presents the following results: there are obstacles that hinder the development of the rules of human rights international law of which the application of fighting terrorism, politicizing the human rights international law, and the idea of New World System are the most important.